Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Patterns or mechanisms? Bergmann’s and Rapoport’s rule in moths along an elevational gradient - J. Beck; H. C. Liedtke; S. Widler; F. Altermatt; S. P. Loader; R. Hagmann; S. Lang; K. Fiedler (Community Ecology, 2016)

Measurements of hydrogen, oxygen and carbon isotope variability in Sphagnum moss along a micro‐topographical gradient in a southern Patagonian peatland - N. J. Loader; F. A. Street‐Perrott; D. Mauquoy; T. P. Roland; S. van Bellen; T. J. Daley; D. Davies; P. D. M. Hughes; V. O. Pancotto; G. H. F. Young; M. J. Amesbury; D. J. Charman; et al. (Journal of Quaternary Science, 2016)
Peat archives offer a diverse range of physical and chemical proxies from which it is possible to study past environmental and ecological changes. Direct numerical calibration and verification is difficult so process‐based and mechanistic studies are therefore required to establish and quantify links between environmental changes and their associated proxy‐responses. Traditional ‘space‐for‐time’ calibrations provide a solution to this calibration problem, but are often unable to isolate a single environmental variable from other potentially confounding variables. In this study, we explored the potential of a site‐specific ‘space‐for‐time’ approach applied to a hummock‐hollow transect on an ombrotrophic raised bog in Patagonia, southern Chile. Coupled stable carbon, oxygen and hydrogen isotopic measurements were made on individual samples of Sphagnum moss cellulose and compared with plant‐associated waters, local hydrology, temperature and relative humidity, sampled at the same points along the study transect. Results reveal a range of environmental responses, which were supported by plant‐physiological models in the case of carbon and oxygen isotopes. For hydrogen isotopes, the results obtained from cellulose indicated a need for further research into hydrogen isotope fractionation in Sphagnum . We recommend conducting site‐specific characterization of plant response to support the development of peat‐based isotope records for palaeoenvironmental research, and where logistically possible, that monitoring is conducted over timescales appropriate to the time‐integrative nature of the Sphagnum record.

Amphibian Diversity in East African Biodiversity Hotspots: Altitudinal and latitudinal Patterns - J. C. Poynton; S. P. Loader; E. Sherratt; B. T. Clarke (Biodiversity and Conservation, 2007)

Refuge use by fish as a function of body weight changes - J. Krause; S. P. Loader; E. Kirkman; G. D. Ruxton (acta ethologica, 1999)